2011
DOI: 10.1124/dmd.111.042028
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variability in Gene Expression Profiles in Human Hepatocytes and Comparison with HepaRG Cells

Abstract: ABSTRACT:Interindividual variations in functions other than drug metabolism activity, remain poorly elucidated in human liver. In the present study, the whole transcriptome of several human hepatocyte populations and the differentiated human HepaRG cell line have been analyzed and compared, using oligonucleotide pangenomic microarrays. We show that, although the variation in the percentages of expressed genes did not exceed 14% among the primary human hepatocyte populations, huge interindividual differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 30 publications
6
44
0
Order By: Relevance
“…Furthermore, SULT1B1 mRNA expression was slightly decreased, but still highly variable. GSTP1 could not be detected in HepaRG cells, as previously shown in the literature (Rogue et al, 2012). Also, in contrast to findings in PHH, the mRNA expression of ABCB1 and ABCC2 was not significantly downregulated, while SLC22A7 was much stronger downregulated (Fig.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, SULT1B1 mRNA expression was slightly decreased, but still highly variable. GSTP1 could not be detected in HepaRG cells, as previously shown in the literature (Rogue et al, 2012). Also, in contrast to findings in PHH, the mRNA expression of ABCB1 and ABCC2 was not significantly downregulated, while SLC22A7 was much stronger downregulated (Fig.…”
supporting
confidence: 67%
“…However, PHH are restricted in availability and have a limited life span. Furthermore, PHH exhibit marked interindividual variations, including variability in expression and corresponding activities of many genes related to drug metabolism (Rogue et al, 2012). The HepaRG cell line has been proposed as an alternative model for PHH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, large interindividual variability has been observed in both the basal expression (Rogue et al, 2012) and in response to treatment of many genes related to drug metabolism. Liguori et al (2005) showed that, after 24 hours of treatment with trovafloxacin, gene changes varied across four different primary human hepatocyte (PHH) cultures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of fresh human hepatocytes has several drawbacks, such as scarce and unpredictable availability, interdonor variability, and significant variation in cell functions, especially cytochrome P450 (P450) activities (Luo et al, 2002;Ohtsuki et al, 2012;Rogue et al, 2012;Schaefer et al, 2012). Today, pooled cryopreserved human hepatocytes from several donors are used routinely in drug discovery and development to overcome the inconsistencies associated with fresh human hepatocytes.…”
Section: Introductionmentioning
confidence: 99%